2021
DOI: 10.3390/agronomy11061129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Generation of Coated Fertilizers to Reduce the Leaching of Mineral Nutrients and Greenhouse Gas (N2O) Emissions

Abstract: The increased use of fertilizers in agriculture and forest and horticulture nurseries contributes to the pollution of water resources and greenhouse gas emissions. The objective of this study is to evaluate a new generation of fertilizers coated with new biodegradable polymers in terms of physical quality, release kinetics, and their effect on reducing nitrate leaching and N2O emissions and compare them to uncoated fertilizers (Urea, monoammonium phosphate (MAP), and KCl) having the same mineral nutrient conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The peak N 2 O fluxes from CK, FP, OPT, CU and CUNI treatments ranged from 9.1 to 21.7, 40.6 to 56.3, 36.3 to 54.0, 21.0 to 41.4 and 19.5 to 39.9 g N ha –1 d –1 , respectively ( Figure 3 ). The peak N 2 O fluxes of EENF treatments appeared 2–8 days later than the first N 2 O peaks of FP and OPT treatments ( Figure 3 ) due to the delayed urea hydrolysis, retarded nitrification and impeded accumulation of NO 3 − in soil via the addition of CRF and NI [ 48 , 53 ], as supported by the lower soil NH 4 + –N and NO 3 − –N contents during the early lettuce growing stage in this study ( Figure 2 ) and previous findings [ 54 , 55 ].…”
Section: Resultssupporting
confidence: 85%
“…The peak N 2 O fluxes from CK, FP, OPT, CU and CUNI treatments ranged from 9.1 to 21.7, 40.6 to 56.3, 36.3 to 54.0, 21.0 to 41.4 and 19.5 to 39.9 g N ha –1 d –1 , respectively ( Figure 3 ). The peak N 2 O fluxes of EENF treatments appeared 2–8 days later than the first N 2 O peaks of FP and OPT treatments ( Figure 3 ) due to the delayed urea hydrolysis, retarded nitrification and impeded accumulation of NO 3 − in soil via the addition of CRF and NI [ 48 , 53 ], as supported by the lower soil NH 4 + –N and NO 3 − –N contents during the early lettuce growing stage in this study ( Figure 2 ) and previous findings [ 54 , 55 ].…”
Section: Resultssupporting
confidence: 85%
“…Polymer coating of the conventional N fertilizers is one of the most effective techniques for reducing N losses and enhancing nitrogen-use efficiency [42]. Benlamlih et al [43] described that biodegradable polymer coated N fertilizers reduced N 2 O and leaching losses of N under heavy rain fall events.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of micronutrients and beneficial microbial strains to major nutrient sources could accelerate the crop performance due to their interaction with major nutrients and improvement in soil health [30]. It has been shown that biodegradable polymer-coated N fertilizers can reduce losses of ammonia and leaching during periods of heavy rain [31].…”
Section: Discussionmentioning
confidence: 99%